Foam flow in porous media: Concepts, models and challenges - Hematpur, H. (Elsevier B.V., 2018)
This paper aims to elaborate foam concepts and foam flow modeling approaches in porous media. Furthermore, this review summarizes and compares all existing foam models approaches including Mechanistic, Semi-Empirical and Empirical. Finally, it discusses foam models in different reservoir simulators in detail and presents different approaches for obtaining modelsâ parameters in simulators. The comparison results showed that Emprical models are more suitable for simulation study due to less required paramters and faster calculation; however, these models might not be a appropriate in transient foam flow. Moreover, the challenges about he results of this review provide an valuble insight about foam behaiviour. Â© 2018 Elsevier B.V.